Translation from, to and within the Atlantic Creoles - Lang, George (TTR, 2000)
AbstractTranslation from, to and within the Atlantic Creoles — Translation involving creóle languages suffers the general disadvantage of writing in creoles: low levels of literacy, the lack of standard orthographies, the overwhelming economic and cultural power of the metropolitan languages with which they compete. The pitfalls attendant to translation in any language are thus aggravated when translating to and from creoles, and these adverse sociolinguistic conditions affect the role of créoles as source and as target languages differently. Another possibility is of course that creoles serve as both SL and TL, and that translation be between or among creóles — a rather rare case. These three eventualities raise several issues of translation theory, in particular the role of shared implicature in languages whose cultures are related (Venuti, 1997). At the same time, certain concepts of translation theory explored recently by Robinson (1997) and others, can shed light upon the particular social and political problems faced by these languages.